Conceptualization and Design of an Efficient Groundwater Recharge System for NIT Kurukshetra. (2016) - Yadav, Manisha; Setia, Baldev
Abstract: National Institute of Technology (NIT) Kurukshetra is a 292-acre campus, having more than 7000 residents on the campus. Due to lack of an efficient drainage system, the campus turns into a system of pools at important locations. This accumulation of water for long durations creates an unhealthy environment for the inhabitants besides damaging the roads, pavement and foundation of buildings. Hence, keeping in view all the above problems and status of the campus, rainwater harvesting can be considered as one of the solutions for addressing the problem of accumulated rainwater in the NIT Kurukshetra. The total area of the campus is 11, 79, 607 sqm, out of which 1, 15, 941 sqm is built up area and rest of the plain area can be utilized for artificial recharge. In this paper, an efficient design of rainwater harvesting system for the campus is proposed. The detailed design of the components of rainwater harvesting through artificial recharge i.e. filter gallery, recharge well, recharge pit, inspection pit etc are provided. It is expected that the result of the study if implemented will certainly fulfill the dual objective of addressing the menace of water logging in the campus besides enriching the groundwater aquifer.